PENGEMBANGAN APLIKASI ENCODING DAN DECODING TREE MENGGUNAKAN KODE DANDELION - Wamiliana Wamiliana; Astria Hijriani; Novi Hardiansyah (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2015)
In this research, we develop The Application of Encoding and Decoding Tree Using The Dandelion Code.Â It aims to obtain Dandelion code of a tree using encoding and decoding. The encoding generates code from a tree, and decoding processes a code back into a tree. This application is developed to produce the best tree representation. Additionally, in this research we give an example of problem that can use Dandelion Code for solving the lowest cost for electricity installation.Keywords : Application, Encoding, Dandelion Code, Decoding, Tree, Tree Representation.